Effect of Romantic Relationship on Implicit Regional Prejudice. (26th April 2014) - Jin, Zheng; Sherman, Jeffrey W.
Abstract: The study measures both the implicit regional prejudice and the explicit simple attitude of 93 students of five universities in China, either involved or not in different stages of a romantic relationship and at varying distances from their partners, by using the Brief Implicit Association Test and Explicit Reports. Results indicate that close relationships can contribute significantly to decreasing implicit regional prejudice. Further studies are needed to provide support for the causal mechanism between interpersonal relationships and changes in social attitudes. Copyright © 2014 John Wiley & Sons, Ltd.